Spatial -Temporal Environmental Conditions of the Makassar Strait Waters 2020-2023 - Putri, Rini Sahni; Hasrianti, Hasrianti; Idrus, Muh. Ikhsan (Jurnal Sains dan Teknologi Perikanan, 2025)
The condition of the aquatic environment plays a very important role in the success of fisheries because various environmental factors directly affect the growth, reproduction, and survival of fish. Factors such as water temperature, chlorophyll, currents and others, contribute to fisheries productivity. This study aims to provide a spatial and temporal overview of the environmental conditions of the Makassar Strait waters in 2020-2023. This study uses AQUA MODIS remote sensing satellite data to map the environmental conditions of the Makassar Strait waters in 2020-2023 spatially and temporally. Data analysis uses Geographic Information Systems (GIS) and interpolation using the Inverse Distance Weighting (IDW) method. The results of this study indicate that the spatial distribution of sea surface temperatures in the Makassar Strait waters fluctuates both spatially and temporally between 25.0°C – 33.9°C. The lower range at the beginning of the year is January-February and starts to get warmer in March-June, then returns to low or cold in July-September and warms up again until the end of the year reaching 33°C around the waters of Pinrang, Parepare, Barru and Pangkajene Islands. The current speed is in the range of 0.1-0.7 m/s and tends to head north. The spatial-temporal pattern of chlorophyll-a content of the Makassar Strait waters is between 0.10 – 0.99 mg/m³.